(untitled) (Research, Society and Development, 2022)
To evaluate the efficacy of cross-linking agents in strengthening the hybrid layer in decayed dentin when associated with adhesives, and also to compare them with respect to the exclusive use of adhesives. This is an integrative review based on the search for scientific publications indexed in electronic databases conducted in MEDLINE via PUBMED, using the following MeSH terms: dentin; dental caries; proanthocyanidins, riboflavin. At the end of the search, 30 publications met the criteria and were selected for the study. In view of the findings of the selected studies, the formation, stabilization and integrity of the hydride layer is of paramount importance for the effectiveness of adhesion. Enzymatic biodegradation is still reported as a reason for decreased adhesion because, over time, bonds degrade, directly affecting tooth-restoration longevity, thus causing failures and even breakage. However, several studies have brought procedures that aim to reduce this biodegradation, thus improving dentin adhesion and increasing its lifetime. This study allowed us to reflect that some cross-linking agents have been tested for such purposes, where we can mention synthetic, natural, and natural agents with combined action with ultraviolet light, such agents directly affect the inter- and intramolecular covalent bonds, thus resulting in greater resistance to degradation by endogenous proteases.